2009
DOI: 10.1159/000204230
|View full text |Cite
|
Sign up to set email alerts
|

Interferon β-1a Induces Tumor Necrosis Factor Receptor 1 but Decreases Tumor Necrosis Factor Receptor 2 Leukocyte mRNA Levels in Relapsing-Remitting Multiple Sclerosis

Abstract: Objective: Members of the tumor necrosis factor (TNF) receptor superfamily play a major role in the pathogenesis of multiple sclerosis. To elucidate the role of TNF receptors, in 53 relapsing-remitting multiple sclerosis patients, we measured the TNF receptor 1 and receptor 2 (TNF-R1 and TNF-R2) mRNA levels in peripheral blood leukocytes in natural history (n = 27) and during administration of interferon (IFN) β-1a (n = 26). Methods: Every 3 months for the duration of 1 year peripheral blood leukocytes were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Collated with our previous results [15] demonstrating a correlation between TNFR1 mRNA and EDSS in RRMS and thus low TNFR1 expression at the beginning of the disease, and the finding that subcutaneously applied IFN-β increased the amount of TNF-R1 mRNA but partly decreased the amount of TNF-R2 mRNA in clinically and subclinically defined responders to therapy after 1 year compared to baseline levels, the following may be suggested: TRAF2 elevation in RRMS might reflect enhanced proinflammatory signaling by TNFR1, and in particular by TNFR2, which primarily adopts a proinflammatory involvement in leukocytes. Taking the results of Arnett et al [26] into account, which indicate that TNFR2 is critical for oligodendrocyte regeneration, the combination of differential expression values of TRAF2 in CNS tissue and blood leukocytes in MS might run entirely contrary to the result shown for systemic lupus erythematosus, each time taking into account the respective state of the disease.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Collated with our previous results [15] demonstrating a correlation between TNFR1 mRNA and EDSS in RRMS and thus low TNFR1 expression at the beginning of the disease, and the finding that subcutaneously applied IFN-β increased the amount of TNF-R1 mRNA but partly decreased the amount of TNF-R2 mRNA in clinically and subclinically defined responders to therapy after 1 year compared to baseline levels, the following may be suggested: TRAF2 elevation in RRMS might reflect enhanced proinflammatory signaling by TNFR1, and in particular by TNFR2, which primarily adopts a proinflammatory involvement in leukocytes. Taking the results of Arnett et al [26] into account, which indicate that TNFR2 is critical for oligodendrocyte regeneration, the combination of differential expression values of TRAF2 in CNS tissue and blood leukocytes in MS might run entirely contrary to the result shown for systemic lupus erythematosus, each time taking into account the respective state of the disease.…”
Section: Discussionsupporting
confidence: 70%
“…In our recent study, in RRMS, we revealed a correlation between the expanded disability status scale (EDSS) score and the TNF-R1 mRNA level in leukocytes. Additionally, subcutaneously applied IFN-β increased the amount of TNF-R1 mRNA, but partly decreased TNF-R2 mRNA expression in clinically and subclinically defined responders to therapy after 1 year compared to the baseline value [15]. We performed quantitative reverse transcription polymerase chain reaction (RT-PCR) to investigate leukocyte TRAF2 and RIP expression in MS patients for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…IFNγ and TNFα are usually deemed proinflammatory. However, there is also evidence for a double-sided ‘Janus' role of both TNFα and IFNγ in chronic autoimmune inflammation and MS [66,70,71,72], and it has been proposed that the TNFα/IL-6 balance is of importance for the therapeutic effect of the IFNβ treatments [73]. The relationship between changes in EDSS scores and IFNγ/IL-6 ratio in our study groups (compare fig.…”
Section: Discussionmentioning
confidence: 59%
“…Taking into account several roles of FADD [8] collated with our previous results [15], this may suggest the following notion: FADD elevation in RR MS might reflect enhanced proinflammatory signaling in peripheral blood leukocytes, but at later stages of the disease or in SP MS TNFR1 signaling that is then predominant rather signals apoptosis. …”
Section: Discussionmentioning
confidence: 65%
“…In multiple sclerosis (MS), a reduction in leukocyte apoptosis might contribute to enhanced migration of autoreactive T cells into the CNS and perpetuation of inflammation [14], resulting in clinical and subclinical exacerbations. Recently, we have succeeded in demonstrating that in natural history in relapse remitting (RR) MS there is a correlation between the expanded disability status scale (EDSS) score and the TNF-R1 mRNA level in leukocytes [15]. Here, we performed quantitative reverse transcription polymerase chain reaction (RT-PCR) to investigate leukocyte TRADD and FADD expression in MS patients for the first time.…”
Section: Introductionmentioning
confidence: 99%